Social Equity in Professional Codes of Ethics. (2nd September 2020) - McCandless, Sean; Ronquillo, John C.
Abstract : Social equity is a principle of public administration ethics and is reflected in numerous professional organizations' codes of ethics. This piece examines social equity as an ethical imperative of public administration by examining the purposes of codes, surveying the meanings of social equity, and exploring how social equity is present in 10 codes, with particular focus on the American Society for Public Administration (ASPA). Reflections are offered on social equity as an ethical principle of the field.